การมีส่วนร่วมในกิจกรรมนักศึกษาของนักศึกษาต่างชาติ คณะวิทยาการอิสลาม มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี - ยาฮารี กาเซ็ง (มหาวิทยาลัยสงขลานครินทร์, 2023)
The purposes of this research are 1) To study the activities organizations that international students are interested and want to participate. 2) to study the factors affecting international students in activities participation. 3) to study the comparison of activities participation of international students by gender, country and class study. 4) to propose guidelines promoting international students' activities participation. The research surveyed 55 Faculty international students of Islamic Sciences (FaIS), Prince of Songkla University (PSU), Pattani Campus. The research tools and quality testing was a questionnaire and a focus group discussion of 33 students. Statistics in this research used frequency, percentage, standard division and presented a table for an explanation.